The Evolution of Cyber War : International Norms for Emerging-Technology Weapons - Mazanec, Brian M. (Book collections on Project MUSE., 2015)
"In January 2014 Pope Francis called the Internet a "gift from God." Months later former Secretary of Defense, Leon Panetta, described cyber warfare as "the most serious threat in the 21st century," capable of destroying our entire infrastructure and crippling the nation. Already, cyber warfare has impacted countries around the world: Estonia in 2007, Georgia in 2008, and Iran in 2010; and, as with other methods of war, cyber technology has the ability to be used not only on military forces and facilities, but on civilian targets. Our computers have become spies and tools for terrorism, and a have allowed for a new, unchecked method of war. And yet, cyber warfare is still in its infancy, with inumerable possibilities and contingencies for how such a war may play out in the coming decades. Cyber War Taboo?: The Evolution of Norms for Emerging-Technology Weapons, from Chemical Weapons to Cyber Warfare examines the international development of constraining norms for cyber warfare and predicts how those norms will unfold in the future. Using case studies for other emerging-technology weapons--chemical and biological weapons, strategic bombing, and nuclear weapons--author Brian Mazanec expands previous definitions of norm evolution theory and offers recommendations for citizens and U.S. policymakers and as they grapple with the impending reality of cyber war"--